Identification Of Weak Buses In Electrical Power System Based On Modal Analysis And Load Power Margin - Mohamad Nor, Ahmad Fateh; Sulaiman, Marizan (Asian Research Publishing Network (ARPN), 2019)
This paper presents the identification of weak buses in electrical power system with the use of modal analysis technique and load power margin values. A weak bus can be defined as a load bus that has high tendency towards experiencing voltage instability. This type of bus cannot afford high value of load incremental values. The modal analysis technique will show the list of weak buses in the power system. Meanwhile load power margin is very useful for showing how much the load at the bus can be increased before experiencing voltage instability. Both modal analysis technique and load power margin values are applied upon the IEEE 39-bus test power system. From there, five weak buses in the test power system are selected and compared. The results proved that weak buses determined by modal analysis technique have low load power margin values.